Level of customer satisfaction towards service quality in the management of Al-Baghdadi learning centre Sungai Besi, Selangor / Nurul Izzaty Mohamad Ridzuan - Mohamad Ridzuan, Nurul Izzaty (2017)
The primary objective of this study is to identify the level of customer satisfaction towards the service quality in the management of Al-Baghdadi Learning Centre Sungai Besi, Selangor. The study wanted to determine the most critical elements in the control, which may be used to review the characteristics or features of the administration and services provided as experienced by customers. The study mentioned above no research has yet investigated. A review of the literature was conducted to find out the relationship between service quality and customer satisfaction. The literature review confirms this relationship. A survey was conducted to collect data. The sample size of 100 Al-Baghdadi Learning Centre Sungai Besi customers was described. The result shows that all the service quality elements are positively related to customer satisfaction in the management of Al-Baghdadi Learning Centre Sungai Besi, Selangor. This study suggests that service quality model also known as SERVQUAL is a suitable instrument for measuring the elements of service quality. Therefore, the managers can use this instrument to improve the management service quality at Al-Baghdadi Learning Centre Sungai Besi.